The Evolving Landscape of e-Cigarettes: A Systematic Review of Recent Evidence - Bozier, J.; Chivers, E.K.; Chapman, D.G.; Larcombe, Alexander; Bastian, N.A.; Masso-Silva, J.A.; Byun, M.K.; McDonald, C.F.; Crotty Alexander, L.E.; Ween, M.P. (ELSEVIER, 2020)
© 2020 American College of Chest Physicians